A Case of Chronic Schizophrenia Who were Switched from Combined Treatment to Monotherapy and Achieved a Decrease in Positive Symptoms after Lowering the Clozapine Dose. Issue 3 (1st September 2016) - Hamurcu, Hayriye Dilek; Caykoylu, Ali; Peksen, Eda; Ozturk, Mehmet; Sevil, Neslihan
ABSTRACT: Despite the limited evidence to support the combination of antipsychotics in treatment resistant schizophrenia in the literature, this situation is common in clinical practice. Treatment guidelines recommend monotherapy for schizophrenia primarily. In this article, a chronic schizophrenic case whose treatment is changed from combination of clozapine with aripiprazole to clozapine monotherapy and whose positive symptoms decreased with the decrease of clozapine doses 900 mg/day to 625 mg/day is reported.